Addressing the Threat of Local Drone Kamikazes to Strengthen National Airspace Defense and Security - Saputro, Wisnu; Taufik, Robby Moehammad; Aritonang, Sovian (UNIVERSITAS PAKUAN, 2025)
The emergence of drone kamikazes as an effective and efficient means of destroying ground targets from the air has been a global concern, especially since Russia's airstrikes on Ukraine in 2022. This technology introduces a new dimension in modern warfare, presenting significant challenges to the defense and security of national airspace. In addition to being effective in destroying targets, the use of drones is also very efficient in terms of the cost of conducting air operations compared to air campaigns using fighter aircraft. Ultimately, drone kamikaze attacks also have the potential to be used in asymmetric attacks, including attacks carried out by insurgent in peacetime. Anticipating this, a new strategic approach is urgently needed to protect national vital objects and secure very important persons (VIPs). The resulting perspective identifies the vulnerability of air defense systems to the swarm tactics and stealth approaches used by drone kamikazes. This paper highlights the importance of integrating advanced technologies, such as artificial intelligence, radar systems and electronic warfare capabilities to effectively detect, intercept, and neutralize drone kamikaze threats , especially those of the fixed-wing drone type . In addition to the technical aspect, the importance of coordinated collaboration between domestic stakeholders and international cooperation to overcome the proliferation of drone technology considering that fixed-wing drone technology can already be produced locally. By adopting a layered air defense strategy, it also offers a holistic approach that includes proactive threat detection, resilient defense systems, and adaptive strategic response and underscores the need for continuous innovation to keep pace with technological developments and drone kamikaze attack tactics in delivering important insights for policymakers, defense strategists, and security professionals in Plan A strong national air defense framework to reduce the risk of kamikaze drone threats , especially domestically made fixed-wing kamikaze drones.